Health information literacy awareness and capacity building: Present and future. (October 2019) - Ottosen, Terri; Mani, Nandita S.; Fratta, Megan N.
Health literacy is increasingly important in today's complex information ecosystem, both nationally and globally. Across the world, whether people live in "information rich" or "information poor" societies, the role of our profession is a vital one. In the developed world, the ubiquitous nature of health information creates a wealth of accessible content and simultaneously has created confusion as to what information is reliable, how health information can be utilized, and whether or not information is produced in a meaningful manner. In the developing world, content may be non-existent, culturally inappropriate or inaccessible in terms of language and other barriers. In order to mitigate the health information crisis we are now facing, we need to collaborate and respond to the challenges raised by the complexity of health information. Librarians and other information professionals can and must play an important role in improving health literacy in their communities. This paper considers international efforts towards improving health in both information poor and information rich settings, including work showcased in recent years at IFLA's Health & Biosciences Libraries Section Open Sessions at the World Library & Information Congress (WLIC). It discusses health literacy in the US and other developed economies, and looks in detail at innovative work by the University of North Carolina at Chapel Hill (UNC)where the Health Sciences Library (HSL), a part of the University Libraries, has strengthened efforts surrounding health literacy in local communities and throughout the state. This paper provides examples of how to partner with multiple constituencies on health literacy and discusses future opportunities for growth and engagement.